Fundamental Considerations of Three-Level DC-DC Converters: Topologies, Analyses, and Control - Xinbo Ruan; Bin Li; Qianhong Chen; Siew-Chong Tan; Tse, C.K. (IEEE transactions on circuits and systems. I, Regular papers, 2008)
This paper discusses the basic family of three-level (TL) dc-dc converters. The origin of TL converters and their basic topological variations are described. Systematic procedures leading to improved and simplified circuit topologies are discussed. A feedforward control scheme that ensures the proper functioning of these converters is proposed. Moreover, the virtues and drawbacks of these converters as compared to conventional converters are highlighted. In particular, the advantages of TL converters include reduced voltage stress of the switches, reduced filter size, and improved dynamic response. It is shown that TL converters are highly suitable for high input/output voltage and medium-to-high-power dc-dc power conversions.